What Makes a Song Trend? Cluster Analysis of Musical Attributes for Spotify Top Trending Songs - Al-Beitawi, Zayd; Salehan, Mohammad; Zhang, Sonya (Journal of Marketing Development and Competitiveness, 2020)
Music streaming services like Spotify have changed the way consumers listen to music. Understanding what attributes make certain songs trendy can help services to create a better customer experience as well as more effective marketing efforts. We performed cluster analysis on Top 100 Trending Spotify Song of 2017 and 2018, using nine musical attributes, including danceability, energy, loudness, speechiness, acousticness, instrumentalness, liveness, valence, and tempo. The results show that music structures with high danceability and low instrumentalness increase the popularity of a song and lead them to chart-topping success.